The name Maria in language and culture - Kuć, Joanna (Papers in Linguistics, 2021)
Personal names are part of legal and moral traditions of each society. They preserve various elements of material and spiritual culture. A genetic link between names and language manifests itself in the lexical and grammatical system. Names function in society as one of the components of culture. The name Maria appears in its original function – as a personal name, but also as a base of secondary names: surnames, geographical names (local, toponyms), participating in the cultural and linguistic onomasticon with multiple meanings.